2015
DOI: 10.1186/s13567-014-0136-1
|View full text |Cite
|
Sign up to set email alerts
|

The early intestinal immune response in experimental neonatal ovine cryptosporidiosis is characterized by an increased frequency of perforin expressing NCR1+ NK cells and by NCR1− CD8+ cell recruitment

Abstract: Cryptosporidium parvum, a zoonotic protozoan parasite, causes important losses in neonatal ruminants. Innate immunity plays a key role in controlling the acute phase of this infection. The participation of NCR1+ Natural Killer (NK) cells in the early intestinal innate immune response to the parasite was investigated in neonatal lambs inoculated at birth. The observed increase in the lymphocyte infiltration was further studied by immunohistology and flow cytometry with focus on distribution, density, cellular p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 59 publications
2
23
0
Order By: Relevance
“…The role of NK cells during C. parvum infection has been studied in ovine, murine and human models of cryptosporidiosis. Within the first few days following infection of 1 day old lambs with C. parvum , the abundance of NKp46+ NK cells expressing CD16, CD25 and perforin was increased in the gut [ 114 ]. In mice, it was demonstrated that oocyst shedding was higher in C. parvum -infected Rag 2 −/− γ c −/− mice (mice lacking B, T and NK cells) compared with C. parvum -infected Rag2 −/− mice (mice lacking B and T cells).…”
Section: Immunology Of Cryptosporidiosismentioning
confidence: 99%
See 1 more Smart Citation
“…The role of NK cells during C. parvum infection has been studied in ovine, murine and human models of cryptosporidiosis. Within the first few days following infection of 1 day old lambs with C. parvum , the abundance of NKp46+ NK cells expressing CD16, CD25 and perforin was increased in the gut [ 114 ]. In mice, it was demonstrated that oocyst shedding was higher in C. parvum -infected Rag 2 −/− γ c −/− mice (mice lacking B, T and NK cells) compared with C. parvum -infected Rag2 −/− mice (mice lacking B and T cells).…”
Section: Immunology Of Cryptosporidiosismentioning
confidence: 99%
“…CD8+ T cells, alongside CD4+ T cells and γδ T cells, are present at an increased frequency within the ileum of C. parvum -infected calves at day 3 post-infection, compared with tissues from uninfected calves [ 118 ]. Furthermore, following infection of 1 day old lambs with C. parvum , CD8+/NKp46− lymphocytes (which the authors concluded were most likely to be CD8+ T cells) were significantly increased in the small intestine at day 3 and day 6 post infection, reflecting their recruitment following infection [ 114 ]. Therefore, CD8+ T cells appear to be involved in the immune response after infection of calves and lambs with C. parvum.…”
Section: Immunology Of Cryptosporidiosismentioning
confidence: 99%
“…As a major component of the innate immune system, natural killer cells are responsible for activating the cytolytic killing of foreign pathogen infection, primarily in defenses against virus, bacteria and parasite during early infection [ 30 ]. Here, we have shown that genes encoding the activator of NK cells (KIR2DS1, KLRJ1) were markedly up-regulated in the intestine tissue of CE infection sheep at 4-hour post infection, suggesting that NK cells might be strongly activated, and thus pose a high cytotoxic potential very early during infection, which is supported by the high expression of MPTX gene encoding mucosal pentraxin.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in partial agreement with reports on sheep C . parvum infection, showing the highly activation of NK cells in the intestine tissue during the very early stage [ 30 ]. Although E .…”
Section: Discussionmentioning
confidence: 99%
“…Both studies found that NK cell-dependent protection was primarily mediated through IFN-γ. Drouet and colleagues recently found an increase in early recruitment of activated, perforin+ NK cells to areas of infection in neonatal lambs infected with C. parvum (66)*. These studies suggest that the role of NK cells during Cryptosporidium infection may involve both IFN-γ-mediated protection and direct cytolysis.…”
Section: Immune Responses To Cryptosporidiummentioning
confidence: 96%